Study on lipid and phospholipid composition from the seed oil of Dalbergia tonkinensis - Thuy, Nguyen Thi; Quan, Pham Minh; Long, Pham Quoc; Dung, Dao Thi Kim; Mai, Nguyen Thi; Vi, Duong The; Diep, Nguyen Thi; Phuong, Doan Lan (Vietnam Journal of Science and Technology, 2023)
The content and composition of classes and molecular species of phospholipid extracted from Dalbergia tonkinensis Prain (Cây Sưa) seed oil in Viet Nam have been investigated using HPLC-HRMS and LCMS-IT-TOF. The content of phospholipid subclasses and their molecular species of D. tonkinensis seed oil have been investigated for the first time. The results showed that D. tonkinensis seed oil contains all basic classes of lipid: polar lipid, sterol, triacylglycerol, free fatty acid, diacylglycerol, hydrocarbon, and wax. In which, the content of triacylglycerol accounts for the highest percentage of 76.38 %, while polar lipid and free fatty acid also have a relatively high content. This result indicated the presence of 12 specific phospholipid subclasses of the plant, including phosphatidylethanolamine, phosphatidylcholine, and phosphatidylinositol. The "molecular forms" of phospholipids of Sua seeds lipids have been identified. The results show that the phospholipids of Sua seeds have 3 classes of substances including phosphatidylethanolamine (PE), phosphatidylcholine (PC), phosphatidylinositol (PI). In which PE has 5 molecular forms, PC has 5 molecular forms and has 2 molecular forms of PI. These are the first data was found and published in Sua seeds.